Inovasi Pemanfaatan Buah dan Sayur Menjadi Smoothie Drink Untuk Meningkatkan Imunitas Tubuh di Masa Pandemi Covid-19 - Nur Syahraeni; Fuad AKbar (Universitas Hasanuddin, 2021)
One form of community service at the college level is real work (KKN) lectures. KKN is a form of activity where community service is performed by the student as well as off-the-books and off-the-books. The success of activities carried out by students can be seen from the benefits people feel after the work program. At this level of unhas wave of 105, students are called upon to create a work program related to the theme